Asymmetric connectedness and investment strategies between commodities and Islamic banks: Evidence from gulf cooperative council (GCC) markets - Billah M; Hadhri S; Shaik M; Balli F (Elsevier B V, 2024)
The study uses the data of thirteen Islamic Banks (IB) in the GCC region and sixteen commodities that include soft agriculture, energy, industry, and precious metal commodities. Murabaha transactions makes up most of the revenues of the Islamic banks, whereas commodities set up the biggest portion of the assets among Murabaha transactions, therefore commodities and IB revenues are expected to comove. Interestingly, empirical findings suggest that most of the Islamic banks and commodities are not significantly affected by the shocks from other markets. We further observe that negative shocks have a higher impact on market connectedness among used assets compared to the positive returns and find a significant role of risk variables in explaining the magnitude of spillover between used assets. We perform robustness of our results in sub-samples periods during Shale Oil Revolution, Global Financial Crisis, and the COVID-19. Additionally, the multivariate portfolio analysis shows some risk reduction properties of the majority of the used assets. The performance evaluation measures demonstrate that weights selected based on dynamic connectedness network presents diversification opportunities. These findings help investors and portfolio managers to remain alert to the movements of the risk factors and calibrate there hedging and portfolio management strategies by taking long and short positions as incorporation of Islamic banks and commodities in the GCC region in a portfolio could yield risk reduction benefits and profitability.
Keywords: Islamic banks; Commodities; GCC markets; Asymmetric connectedness; Crisis periods